2009
DOI: 10.1093/ije/dyn251
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche, total mortality and mortality from ischaemic heart disease and stroke: the Adventist Health Study, 1976-88

Abstract: The results suggest that there is a linear, inverse relationship between age at menarche and total mortality as well as with ischaemic heart disease and stroke mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
130
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 40 publications
12
130
2
1
Order By: Relevance
“…This effect may be due to changes in the socioeconomic and demographic environment, possibly acting through changes in nutrition and exercise patterns [26]. There is evidence that younger age at menarche might lead to certain chronic diseases [8][9][10]12]. Whether this secular trend in puberty timing is really associated with adverse health implications still needs to be assessed [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may be due to changes in the socioeconomic and demographic environment, possibly acting through changes in nutrition and exercise patterns [26]. There is evidence that younger age at menarche might lead to certain chronic diseases [8][9][10]12]. Whether this secular trend in puberty timing is really associated with adverse health implications still needs to be assessed [27].…”
Section: Discussionmentioning
confidence: 99%
“…Age at menarche was shown to be associated with higher BMI [4][5][6][7], cardiovascular disease [8][9][10], metabolic risk factors [4], the metabolic syndrome [11][12][13] and mortality [9,11,12]. Only a few studies have focused on the complex relationship between age at menarche and diabetes mellitus, with different results [5][6][7]14].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the mean age at menarche decreased from 13.2 years in 1961 to 12.2 years in 2011 in school‐aged girls1. Earlier‐onset menarche is reported to be associated with obesity2, 3, 4, 5, type 2 diabetes mellitus4, 6, 7, 8, 9, 10, 11, cardiovascular disease4, 12, 13, 14, breast cancer15 and increased all‐cause mortality4, 13, 16, 17, 18. It is therefore possible that age at menarche can provide important information to help prevent non‐communicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1 The timing of menarche has been reported to influence cardiovascular and metabolic health in adolescence and young adulthood, [2][3][4] but its long-term impact on vascular health in middle-age is unclear. Several studies have suggested that early menarche is associated with increased risk of coronary heart disease [5][6][7][8][9][10][11] or stroke, 7 but findings have been inconsistent. [11][12][13] Some studies have shown associations between early menarche and coronary heart disease only among nonsmokers, [9][10][11] whereas others have not adequately accounted for adult adiposity 6,7,9,12 which is known to be associated with early menarche.…”
mentioning
confidence: 99%
“…Several studies have suggested that early menarche is associated with increased risk of coronary heart disease [5][6][7][8][9][10][11] or stroke, 7 but findings have been inconsistent. [11][12][13] Some studies have shown associations between early menarche and coronary heart disease only among nonsmokers, [9][10][11] whereas others have not adequately accounted for adult adiposity 6,7,9,12 which is known to be associated with early menarche. [14][15][16][17] Some suggested a nonlinear association between menarcheal age and coronary heart disease risk, 6,7 but these studies could not examine variation in risk of coronary heart disease or of other vascular diseases over a wide range of menarcheal ages because numbers of events were generally small.…”
mentioning
confidence: 99%